(untitled) (Fiep Bulletin - online, 2014)
Groups of young sportswomen (track and field, basketball, handball and volleyball) were tested for selected coordination skills. Sufficient amount of test subjects (n = more than 200 in each age group) allows us to monitor changes in the age of balance, orientation, rhythm, reaction and space-orientation skills. The test results were compared with general population of the same age group. Based on these results, we are able to formulate conclusions for training practice in these age groups.